The protective effect of various forms of Nigella sativa against hepatorenal dysfunction: underlying mechanisms comprise antioxidation, anti- inflammation, and anti-apoptosis - Algheshairy, Reham M.; Alharbi, Hend F.; Almujaydil, Mona S.; Alhomaid, Raghad M.; Ali, Hoda A. (Frontiers in Nutrition, 2025)
IntroductionThe liver and kidney are vital organs that are interconnected, dealing with detoxifying and excreting xenobiotics. They are constantly exposed to oxidative stress, which can cause hepatorenal dysfunction. This study compares two forms of Nigella sativa (NS), NS oil (NSO), and NS seeds (NSS), for the first time, in their ability to mitigate hepatorenal injury induced by azathioprine (AZA), exploring potential underlying mechanisms.MethodsGroup (1): negative control; Group (2): positive control received 15 mg/kg AZA orally. Groups (3, 4, and 5) received 100 mg/kg silymarin (standard reference), 500 mg/kg NSO, and 250 mg/kg NSS, respectively, and were subjected to the same dose of AZA. A one-way analysis of variance was conducted, followed by Mann-Whitney post-hoc analysis.ResultsAdministration of AZA induced hepatorenal dysfunction, evidenced by dyslipidemia, elevations in serum liver enzymes, creatinine, urea, pro-inflammatory cytokines, and cytokeratin-18. Antioxidant enzymes in liver and kidney tissues were reduced, with an elevation in caspase-3 and caspase-9. Both forms of NS significantly balanced serum pro- inflammatory cytokines (14.33 ± 2.33, 15.15 ± 1.64 vs. 24.87 ± 1.87) pg/ml, interleukin-4 (16.72 ± 1.14, 15.95 ± 1.03 vs. 10.64 ± 1.04) pg/ml, and interleukin-10 (19.89 ± 0.69, 18.38 ± 0.38 vs. 15.52 ± 1.02) pg/ml, and downregulated cytokeratin-18 (210.43 ± 21.56, 195.86 ± 19.42 vs. 296.54 ± 13.94) pg/ml for NSO and NSS vs. the positive group, respectively. NSS enhanced liver antioxidant activity (P < 0.05), normalized liver enzymes (P < 0.05, P < 0.01) for alanine aminotransferase and aspartate aminotransferase, respectively, and significantly lessened dyslipidemia (P < 0.05). Liver caspase-3 and caspase-9 improved significantly with NSS, while kidney caspase-3 and caspase-9 improved with NSO. NSO increased kidney glutathione peroxidase and catalase (P < 0.01) and corrected creatinine and urea (P < 0.05). Histopathological observations confirmed the present data.DiscussionConclusively, NSO and NSS mitigated hepatorenal dysfunction responses to AZA through antioxidant, anti-inflammatory, and anti-apoptosis properties that underlie their protective performance. Interestingly, NSO surpassed NSS in restoring renal oxidative damage, while NSS provided better hepatic protection than NSO, suggesting NSO for patients with kidney dysfunction and NSS for those with liver problems.